2018
DOI: 10.5539/sar.v8n1p33
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenetic Studies of Some Genotypes of Onion (Allium cepa L.) In Jos, Nigeria

Abstract: The improvement of the fresh bulb and the economic dry matter yields of onion is dependent on the morphogenetic variability and the interrelationships amongst morphological attributes which can be used to determine the quality or performance of the crop. This research was aimed to study the morphogenetic characteristics of ten genotypes of onion (Ares, Violet de Galmi, Red Creole, “Wase”, “Dan Zaria”, “Dan Garko”, “Dan Giyawa”, &am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…The variation in plant height might be due to genetic causes. The present result corroborates the findings of Walle et al [7] and Sirajo and Namo [10].…”
Section: Plant Heightsupporting
confidence: 93%
See 2 more Smart Citations
“…The variation in plant height might be due to genetic causes. The present result corroborates the findings of Walle et al [7] and Sirajo and Namo [10].…”
Section: Plant Heightsupporting
confidence: 93%
“…The apparent cause of the variation in bulb weight among the varieties might have been due to their genetic potential. The similar results have also been reported by Sirajo and Namo [10].…”
Section: Individual Bulb Weightsupporting
confidence: 91%
See 1 more Smart Citation
“…The Buton cultivar showed the highest chromosome size, while the Bombana cultivar showed the lowest chromosome size. Research conducted by [12] showed that there were variation in the length of the chromosome of 10 shallot genotypes, which the highest chromosome length was 12.861±1.257 µm, while the lowest chromosome length was 12.499±0.445 µm. Variation in chromosome length were determined by the length of base pairs in the DNA of each chromosome.…”
Section: Resultsmentioning
confidence: 99%